Integration of Physiotherapy in Healthy and Sustainable Ecotourism: A Case Study of River of Mudal Ecotourism - Wisnu Budi Waluyo; Wing Umi Latifah; Bagus Dwi Hendrawan (Eduvest - Journal of Universal Studies, 2026)
Amid the growing public interest in tourism that is not only refreshing but also provides health benefits, the integration of nature-based physiotherapy services represents a strategic innovation. This study examines the implementation of physiotherapy concepts within healthy and sustainable ecotourism, emphasizing the use of nature-based therapy at Sungai Mudal Ecotourism (ESM) in Kulon Progo, Special Region of Yogyakarta. Ecotourism is generally analyzed from environmental and socio-economic perspectives; however, its potential contribution to health promotion and rehabilitation remains underexplored. Given its natural assets, ESM serves as a relevant example of incorporating physiotherapy activities into ecotourism practices. This study employed a qualitative case study design, utilizing participatory field observations, in-depth interviews, focus group discussions (FGDs) with ESM managers, document analysis of reports and related literature, tourist perception surveys, and light intervention studies on the benefits of therapy-based tourism activities. The results indicate that the natural environment, including rivers, waterfalls, and natural pools, provides opportunities for therapeutic activities such as hydrotherapy and musculoskeletal mobility exercises. These activities benefit both physical and mental health, thereby enhancing the attractiveness and sustainability of ecotourism. This study presents the paradigm of “healthy ecotourism,” which integrates physiotherapy-oriented environmental therapy techniques into ecotourism planning and management. Such integration encourages ESM to strengthen ecotourism sustainability through service diversification, support for local livelihoods, and the reinforcement of health–environment linkages.